Governing Through Patronage: The Rise of NGOs and the Fall of Civil Society in Palestine and Morocco - Atia, Mona; Herrold, Catherine E. (Voluntas (Manchester, England), 2018)
This article examines foreign aid and government funding to NGOs as forms of patronage and explores the impact of such funding on the nature and role of civil society. Using qualitative research from Palestine and Morocco, we argue that patronage transforms NGOs into apparatuses of governing. NGOs become key sites for the exercise of productive power through the technologies of professionalization, bureaucratization, and upward accountability. The article explores how this transformation of NGOs depoliticizes their work while undermining their role as change agents within civil society. The findings have implications for understanding the transformation of NGOs, the relationship between patrons and their grantees, and, finally, for exploring the limitations of NGOs as vehicles for social change in sensitive political environments.